The development of a nursing technology: making visible the nursing contribution to the development of critical care - Crocker, Cheryl (2006)
In the context of one Intensive Care Unit (ICU) and one High Dependency Unit (HDU), this thesis explores and analyses the nursing contribution to the development of critical care. This comprises over more than half a century, focussing on nurses' relationship with, and perceptions of one 'technology', weaning from mechanical ventilation, as part of everyday nursing practice in the new millennium. My findings suggest that nurses take a task-focussed approach to weaning, treating it as a `medical' technology transferred to them from doctors, rather than seeing its potential to become a ‘nursing technology' in which the nurse is enabled to transform weaning into a way of implementing care in order to improve patient outcomes. Analysis demonstrates when nurses work in this way weaning is delayed and as a result patients will be exposed to greater morbidity and mortality.